Structure and performance of infectious disease surveillance and response, United Republic of Tanzania, 1998 - Nsubuga Peter; Eseko Nicholas; Tadesse Wuhib; Ndayimirije Nestor; Stella Chungong; McNabb Scott (The World Health Organization, 2002)
OBJECTIVE: To assess the structure and performance of and support for five infectious disease surveillance systems in the United Republic of Tanzania: Health Management Information System (HMIS); Infectious Disease Week Ending; Tuberculosis/Leprosy; Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome; and Acute Flaccid Paralysis/Poliomyelitis. METHODS: The systems were assessed by analysing the core activities of surveillance and response and support functions (provision of training, supervision, and resources). Data were collected using questionnaires that involved both interviews and observations at regional, district, and health facility levels in three of the 20 regions in the United Republic of Tanzania. FINDINGS: An HMIS was found at 26 of 32 health facilities (81%) surveyed and at all 14 regional and district medical offices. The four other surveillance systems were found at <20% of health facilities and <75% of medical offices. Standardized case definitions were used for only 3 of 21 infectious diseases. Nineteen (73%) health facilities with HMIS had adequate supplies of forms; 9 (35%) reported on time; and 11 (42%) received supervision or feedback. Four (29%) medical offices with HMIS had population denominators to use for data analyses; 12 (86%) were involved in outbreak investigations; and 11 (79%) had conducted community prevention activities. CONCLUSION: While HMIS could serve as the backbone for IDSR in the United Republic of Tanzania, this will require supervision, standardized case definitions, and improvements in the quality of reporting, analysis, and feedback.